Phosphorylated-calix[4]arene double-deckers of single rare earth metal ions. Issue 65 (25th July 2021) - Hosseinzadeh, Marjan; Sanz, Sergio; van Leusen, Jan; Izarova, Natalya V.; Brechin, Euan K.; Dalgarno, Scott J.; Kögerler, Paul
Abstract : Phosphorylation of calix[4]arenes imparts an increased solubility and facilitates drastically changed coordination toward lanthanide ions, resulting in mononuclear double–decker complexes. Abstract : Combination of phosphoryl and calix[4]arene moieties in the same organic framework (LPO ) directs the formation of homoleptic double–decker complexes [Ln III (LPO )2 ](OTf)3 for Ln = Tb and Dy, with the latter displaying slow relaxation of the magnetisation.